Socialism and Development in Ethiopia : a critical examination of the military regime's socialist agricultural program - Makonen Getu (Regnum studies in mission., 2015)
This study identifies and analyzes the methods, achievements, and constraints of the socialist agricultural policy of post-revolutionary Ethiopia. It investigates the Land Reform Legislation of 1975 and its relevance to Ethiopian conditions at that time. Applying a social interaction approach, this book examines the interrelationships of the different socio-economic actors who affected the success and shortcomings of the policy and its implementation. Through critical consideration of a historical period, this book also uncovers applicable lessons for future achievable development in Ethiopia and similar economies.